DEVELOPMENT OF ARCHITECTURAL MODEL OF UNIVERSAL RECORDING SERVICE DEALER SYSTEM SCRIPT - Alexandra Y. Skornyakova (Статистика и экономика, 2016)
In the present article there is a review ofthe development of architectural modelof universal recording service dealersystem script, the use of pattern «Factory» to solve the problem in adding newdealerships is discussed and a possibleoptimized system model is suggested.